EVALUASI PENGGUNAAN ANTIBIOTIK YANG RASIONAL PADA PASIEN PNEUMONIA RAWAT INAP DI RS X KOTA CIREBON - Rahmi Nurhaini; Tomi Tomi; Afifah Faradhila; Iin Indawati (CERATA Jurnal Ilmu Farmasi, 2023)
Antibiotics are the main therapy for pneumonia caused by bacteria. Inappropriate use of antibiotics leads to resistance. The purpose of this study was to describe the charateristics (gender, age, and payment status), the rationale for the use of antibiotics including the parameters of the right indication, the right patient, the right dose, and the right route of drug which refers to Permenkes number 28 of 2021 in pneumonia patients in the inpatient installation of RS X Kota Cirebon. This research is an observational study with retrospective data collection techniques through medical records. Sampling was done done by purposive sampling. The sample in this study was the medical recorsd of patients diagnosed with pneumonia who received antibiotic therapy and met the inclusion criteria of 97 medical records. The guidelines used are Permenkes number 28 of 2021 concercing guidelines for the use of antibiotics. Data analysis was carried out descriptively using Microsoft Excel 2019 presented in the form of tables, diagrams and percentages accompanied by explanations. The results of the study showed that the suitability of using antibiotics based on guidelines obtained right indication of 100%, right drug 34%, right dose 50,5%, and right route of drug administration 100%. Data on the number of patients who used antibiotics in pneumonia patients rationally was 23,7% and irrational use was 76,3%.